Analisis Implementasi Good Manufacturing Practices pada Pengendalian Pasca Panen Telur untuk Reduksi Kontaminasi Salmonella sp. : Kajian Literatur - Nabilla Dwi Utami; Odelya Sabrina Putri P; M. Rizky Galan Ramadhan; Sholahuddin Ilham A; Faranita Ratih Listiasari (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Eggs are one of the most widely consumed animal protein sources globally, yet they remain highly vulnerable to microbiological contamination, particularly by Salmonella sp., which poses significant public health risks. This literature review aims to analyze the implementation of Good Manufacturing Practices (GMP) in post-harvest egg handling as a strategy to reduce Salmonella sp. contamination. The review synthesizes findings from national and international scientific journals. The results indicate that post-harvest stages—including collection and grading, storage, packaging, and preservation—are the most critical phases for contamination control. GMP implementation at each stage plays a fundamental role in maintaining egg quality and safety.